Shear‐Driven Direct‐Write Printing of Room‐Temperature Gallium‐Based Liquid Metal Alloys. Issue 11 (16th September 2019) - Cook, Alexander; Parekh, Dishit P.; Ladd, Collin; Kotwal, Gargee; Panich, Lazar; Durstock, Michael; Dickey, Michael D.; Tabor, Christopher E.
Abstract : Gallium‐based metal alloys have high electrical conductivity in the liquid state at room temperature. These liquid metal conductors inspire unique electronic applications such as reconfigurable circuits and stretchable components with extremely high strain tolerance. Previously, liquid metals have been successfully patterned via direct‐writing, yielding metallically conductive features on‐demand at room temperature that do not require post‐processing, down to a resolution of ≈10 μm. While most direct‐write processes extrude materials from a nozzle via pressure or volumetric displacement, liquid metal is instead printed here by a shear‐driven mechanism that occurs when the oxide‐coated meniscus of the metal adheres to the printing substrate and is "pulled" from the nozzle at pressures that are well‐below that needed to extrude the metal in the absence of shear. Herein, the key operating parameters that enable shear‐driven printing of liquid metals including dispensing pressure, choice of substrate, print height, the surrounding environmental conditions, and the speed and acceleration of the print head are elucidated. A guide to the best practices as well as limitations for implementing shear‐driven printing of liquid metals at room temperature is provided in these studies. Abstract : Low‐melting‐point gallium alloys are ideal candidates for direct‐write printed electronics due to the ability to extrude the conductive fluid from a syringe and the fast formation of an oxide skin on the liquid surface. The critical role that the oxide has on the extrusion process itself is demonstrated, and the critical parameters to successfully direct write print gallium alloys are discussed.